Human Resource Strategies for Implementing Diversity and Inclusion in Pekanbaru Organizations - Saiful Anuar; Herispon; Abd. Asis; R. Rudi Alhempi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The implementation of Diversity & Inclusion (D&I) has become a strategic issue for both public and private sector organizations in improving organizational productivity and effectiveness. However, the success of D&I implementation largely depends on the Human Resource Management (HRM) strategies applied. This study aims to analyze HRM strategies in realizing Diversity & Inclusion in public and private organizations in Pekanbaru. The HRM strategies examined include aligning D&I with organizational strategy, implementing fair recruitment and selection policies, providing D&I awareness training and development, creating an inclusive work culture, and monitoring and evaluating D&I initiatives. This research employed a quantitative, descriptive method with multiple linear regression analysis. The sample consisted of 150 employees and organizational leaders selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using descriptive and inferential statistics. The findings indicate that HRM strategies have a significant effect on the successful implementation of D&I, with fair recruitment and selection policies and an inclusive work culture identified as the most influential factors. Meanwhile, D&I training and development, as well as monitoring and evaluation efforts, still require further improvement. This study concludes that aligning HRM strategies with D&I principles is essential for creating inclusive and productive organizations.